Plants, health and healing : on the interface of ethnobotany and medical anthropology - Harris, Stephen , 1966-; Hsu, Elisabeth (Epistemologies of healing, 2010)
Plants have cultural histories, and their culturally known applications change through time and across contexts. The impact of individual plant species on human cultures has been profound, whether it is the coca and quinine from South America or tea and coffee from the Old World. This pattern is seen in all types of uses that humans make of plants